Clients’ Accounts of Resistance in Counselling: A Qualitative Analysis - Rennie, David L. (Canadian Journal of Counselling and Psychotherapy, 2007)
This article is derived from a study of clients' moment-to-moment experience session. Their recollections of the experience were stimulated through the replay of a tape of the session and the transcribed interviews were analyzed in tenus of the grounded theory form of qualitative analysis. The article focuses on accounts given by some of these clients indicating that they were resistant to their counsellor because they were ambivalent about his or her approach to counselling. The returns from the analysis are discussed in terms of current notions of resistance and of the concept of the working alliance in counselling.